2016
DOI: 10.1016/j.neuroimage.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Relation between clinical risk factors, early cortical changes, and neurodevelopmental outcome in preterm infants

Abstract: Relation between clinical risk factors, early cortical changes, and neurodevelopmental outcome in preterm infants, NeuroImage (2016NeuroImage ( ), doi: 10.1016NeuroImage ( /j.neuroimage.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 53 publications
6
48
0
Order By: Relevance
“…This is consistent with a previous observation that elevated cytokines and CD45RO + T lymphocytes in umbilical cord blood are associated with overt cerebral lesions on MRI very soon after birth38. MRI acquisition in the early post-partum period after very preterm birth (around 30 weeks gestational age) is feasible and recent advances in post-processing techniques enable the evaluation of diffuse white matter injury, connectivity measures, cortical maturation and growth trajectories at this early stage394041424344. These approaches could be combined with collateral biological information about fetal/maternal inflammation to investigate specific antenatal determinants of abnormal brain development.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a previous observation that elevated cytokines and CD45RO + T lymphocytes in umbilical cord blood are associated with overt cerebral lesions on MRI very soon after birth38. MRI acquisition in the early post-partum period after very preterm birth (around 30 weeks gestational age) is feasible and recent advances in post-processing techniques enable the evaluation of diffuse white matter injury, connectivity measures, cortical maturation and growth trajectories at this early stage394041424344. These approaches could be combined with collateral biological information about fetal/maternal inflammation to investigate specific antenatal determinants of abnormal brain development.…”
Section: Discussionsupporting
confidence: 90%
“…Given this obstacle to directly compare folding patterns before and after birth, early ex utero imaging of preterm newborns seems to be the only straightforward strategy to allow a continuous description of folding progression before and after term age. Studies on premature newborns have confirmed the dramatic folding increase during the pre-term period (Dubois, et al 2008b;Kapellou, et al 2006;Kersbergen, et al 2016;Kim, et al 2016a;Makropoulos, et al 2015;Rodriguez-Carranza, et al 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Studies in infants born preterm have highlighted the importance of optimal structural volumetric brain growth, with larger white matter and cerebellum being particularly related to better cognition and processing speed at pre‐school age. Impairments in cortical folding at term age are associated with subsequent alterations in cognitive, motor, and language outcome in ex‐preterm infants . It is reasonable to hypothesize that neonatal brain volumes are associated with long‐term outcome in CHD; however, large cohort studies testing this hypothesis are lacking.…”
Section: Macrostructural Brain Development In Fetuses and Infants Witmentioning
confidence: 99%